A COMPARATIVE CLINICAL STUDY ON JARA WITH RESPECT TO AGEING PROCESS WITH ASHWAGANDHA RASAYANA AND MATRA BASTI - Binod Kumar, Singh; D.L, Bharkher (International Journal of Ayurveda and Pharma Research, 2016)
The problem of ageing is experienced by all the countries. According to World Health statistics the life expectancy of Nepalese people has risen from 58.91 years to 67.86 years (1996 to 2015). Ageing is emerging issue in Nepal as well as global. Its tempo is expected to be unexpectedly fast as mortality continues to decline and life expectancy continues to increase. Ayurveda the science of life has observed ageing as a Jara avastha, which is a later phase of life, it is natural, inevitable phenomenon, in which maximum decline of bodily elements that may become as major cause of disability and functional dependency requiring services that affect many sectors of economy, health, security, income, housing, transportation etc. Jara chikitsa has been mentioned as one independent Anga in Ashtanga Ayurveda where Rasayana therapy is capable to impede the ageing process and to delay the degenerative process in the body. In this study we measured the effectiveness of Ashwagandha rasayana and Matra basti and compared with the Ashwagandha Rasayan only in Jara avastha. A total of thirty elderly patients were selected and divided in two groups A and B, given them either Ashwagandha Rasayana with Matra basti or Ashwagandha rasayana in prescribed doses for 45 days. Changes in the subjective complaints, objective parameters of the patients and appearance of adverse events were also evaluated. Both the groups provided better results on the chief complaints But, comparison in between both the groups is insignificant, that may be due to small sample size.